Hubungan Penggunaan Backpack Dengan Kejadian Low Back Pain Pada Mahasiswa Universitas Riau - Etra Fianus Hendri; Ari Pristiana Dewi; Darwin - Karim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the correlation between using of backpack and incidence of low back pain in University of Riau’s student. The design was descriptive correlational research with cross sectional approach. The sampling technique was cluster sampling with 100 respondents which was selected based on inclusion criteria. This research used questionnaire for variable of using backpack and observation sheet for incidence of low back pain. The univariate analysis was done by using distributions of frequencies and bivariate analysis was done by using chi-square test. The result showed, there was the correlation between appropriate backpack, balance, carry less and duration of using backpack with the incidence of low back pain (p value 0,003;0,000;0,000;0,000) and there was no correlation between medical history and incident of low back pain (p value 0,102). According to this research, it is necessary for University of Riau’s student to select appropriate backpack, balance, carry less to reduce the incidence of low back pain. Keywords: Backpack, low back pain, student, University of Riau